Steam car wash gun and vehicle washing system - MA CHENGLING; PANG HONG; QUAN JUNMIN (2018)
The utility model provides a pair of steam car wash gun and vehicle washing system relates to carwash technical field, including barral of a gun and brush head, the brush head sets up the tip at the barral of a gun, the barral of a gun includes steam pump controller, steam pump and pump pole, and steam pump controller and steam pump setting are in the pump pole, steam pump controller is connectedwith the steam pump electricity for the water yield of control steam pump, the brush head has the flowing water passageway including brush holder and apron, brush holder inside, is provided with at least one apopore on the apron, the apron sets up the tip at the brush holder. In above -mentioned technical scheme, steam car wash gun forms through two parts, and the barral of a gun can utilize steampump and pump pole to come the connection and carry water source or vapour source to the transmission capacity of steam pump controller control steam pump is utilized at the in -process of carrying water source or vapour sour